Comparison of Nano Folic Acid and Folic Acid in Performance, Carcass Characteristics, Blood Parameters, and Microbial Population of Broiler Chickens - Ebrahim Shahraki; Mohmmad Kazemi Fard; Mansour Rezaei; Zarbakht Ansari Pirsarai; Mahmoud Barani (پژوهشهای تولیدات دامی)
Extended Abstract Background: The lack of vitamins and minerals, which are lost due to processing, in poultry feed is an important challenge for poultry breeding experts. These nutrients and bioactive substances must be preserved in the feed. Protection of nutrients and vitamins in nano form is one of the most effective ways for health and prevention of diseases in poultry. Folic acid (vitamin B9) is a cofactor of many enzymes, and improper storage conditions or heat from cooking is a factor of its destruction. Due to its antioxidant properties, folic acid oxidizes quickly and has a short shelf life. However, folic acid fortification is the most efficient means of increasing dietary folate intake due to the low intake of folate-rich foods and the excessive loss of folate during processing. Therefore, it is very important to protect this vitamin in the diet. Existing methods to protect nutrients or active ingredients include microencapsulation, spray drying, extrusion encapsulation, fluidized bed coating, conjugation, nanoliposome, and hydrogel encapsulation. Nowadays, the increasing growth of new technologies (nanotechnology) as one of the important sciences in this era, has entered all dimensions and fields of animal, plant, and environmental life and has opened new horizons on the edge of natural sciences. All the physicochemical properties of the material change by changing particle size from micrometer to nanometer (one billionth of a meter) due to the increase in the surface-to-volume ratio. One of the most important methods available to preserve nutrients is the nanoliposome method. Nanoliposomes can usually range from tens of nanometers to several microns. Therefore, this research aimed to investigate the effect of folic acid nanoliposome and folic acid on blood biochemical metabolites and microbial population in the ileum of Ras 308 male broiler chickens. Methods: This study was conducted as a 2 × 2 factorial experiment in a completely randomized design with 250 one-day-old broiler chicks in five treatments with five replicates and 10 observations per replicate. The treatments were a control diet, a folic acid-free diet supplemented with folic acid (4 mg/L of water) in non-nano form, a folic acid-fre diet supplemented with folic acid (4 mg/L of water) in nano form, a control diet supplemented with folic acid (4 mg/L of water) in non-nano form, and a control diet supplemented with folic acid (4 mg/L of water) in nano form. Carcass characteristics, malondialdehyde (MDA) concentration, and bird performance were periodically evaluated during the experiment. Results: Folic acid and nanoliposome folic acid did not significantly affect feed intake, weight gain, and feed conversion ratio (FCR) in the initial period. However, weight gain significantly influenced the interaction effects of folic acid and nanoliposome folic acid compared to the control diet. The addition of folic acid during the growth period significantly increased the weight of broiler chickens (p < 0.05), with a greater increase in folic acid nanoliposome treatment than in the other treatments. The interaction effects of folic acid and folic acid nanoliposome in the growing and finishing periods were significant on feed intake, weight gain, and FCR (p < 0.05). In the growing and final periods, feed intake, weight gain, and FCR increased significantly in the folic acid-free control diet in water (4 mg/L) in the folic acid nanoliposome form compared to the other treatments (p < 0.05). The lowest feed intake, weight gain, and FCR were measured in the control treatment in the growth and final periods compare d to the other treatments. Breast weight increased significantly in the control diet treatment with folic acid in water (4 mg/L) in the folic acid nanoliposome form (p < 0.05). The effect of folic acid was significant on some biochemical parameters, such as protein, albumin, and globulin, compared to the control treatment (p < 0.05). However, nano folic acid significantly increased protein, albumin, globulin, and uric acid (p < 0.05). Therefore, the highest significant amounts of total serum protein, albumin, and globulin belonged to the control diet treatment with the nano form folic acid in water (4 mg/L) (p < 0.05). Cholesterol and glucose concentrations significantly affected the interaction effects of folic acid and folic acid nanoliposome compared to the control diet. Abdominal fat and triglyceride decreased significantly in the control diet treatment with folic acid in water (4 mg/L) in the folic acid nanoliposome form (p < 0.05). However, the highest percentage of abdominal fat and triglycerides were observed in the control treatment. Although normal folic acid and folic acid nanoliposome and their interactions did not significantly influence MDA concentration,, folic acid nanoliposome positively affected the average MDA concentration. Normal folic acid and folic acid nanoliposomes did not significantly affect the microbial population of the ileum. Conclusion: The results of this study showed that encapsulating folic acid in the growth and final periods improved performance, increased breast weight, and decreased abdominal fat.